PENGARUH KOMPOSISI MEDIA TANAM DAN KONSENTRASI GROWMORE TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SELEDRI (Apium graveolens) - Ahmad Sukri; Vonny Indah Sari; Endriani (DINAMIKA PERTANIAN, 2025)
Celery (Apium graveolens) is one of the important vegetable crops with export potential. The cultivation of celery in Riau Province tended to be constrained by low soil fertility, particularly due to the dominance of Yellow Red Podzolic (PMK) soils. To address this issue, efforts to improve yields by selecting suitable growing media and fertilizing were necessary. This study was conducted at the experimental farm of the Faculty of Agriculture, Universitas Lancang Kuning, located on Jl. Yos Sudarso Km 8, Rumbai, Pekanbaru. The site had flat topography, an elevation of 16 meters above sea level, and Yellow Red Podzolic soil. The study was conducted over four months, from July to October 2024. The research used a factorial Completely Randomized Design (CRD) with two factors: M (growing media) with four levels and G (Growmore liquid fertilizer) with four levels. Each treatment was replicated three times, resulting in 48 experimental plots. Each plot contained four plants, with two plants used as samples, giving a total of 192 plants and 25% extra as reserve plants. Based on the analysis of variance, both the composition of the growing media and the concentration of Growmore had significant effects on all observed parameters, which included plant height, number of petioles, plant weight, root volume, and number of tillers. Further analysis showed that the interaction between growing media composition and Growmore concentration significantly affected all treatments. The lowest growth was observed in treatment M0G0 (no media composition and no Growmore fertilizer). At the same time, the highest performance was recorded in treatment M3G3 (PMK soil + rice husk charcoal + goat manure at a 1:1:2 ratio and Growmore fertilizer at 3 g/L).